Targeting autoimmune mechanisms by precision medicine in Myasthenia Gravis - Cavalcante, Paola; Mantegazza, Renato; Antozzi, Carlo (Frontiers in Immunology, 2024)
Myasthenia Gravis (MG) is a chronic disabling autoimmune disease caused by autoantibodies to the neuromuscular junction (NMJ), characterized clinically by fluctuating weakness and early fatigability of ocular, skeletal and bulbar muscles. Despite being commonly considered a prototypic autoimmune disorder, MG is a complex and heterogeneous condition, presenting with variable clinical phenotypes, likely due to distinct pathophysiological settings due to different immunoreactivities, symptoms' distribution, disease severity, age at onset, thymic histopathology and response to therapies. Current treatment of MG based on international consensus guidelines allows to effectively control symptoms, but most patients do not reach complete stable remission and require life-long immunosuppressive (IS) therapies. Moreover, a proportion of them is refractory to conventional IS treatment, highlighting the need for more specific and tailored strategies. Precision medicine is a new frontier of medicine that promises to greatly increase therapeutic success in several diseases, including autoimmune conditions. In MG, B cell activation, antibody recycling and NMJ damage by the complement system are crucial mechanisms, and their targeting by innovative biological drugs has been proven to be effective and safe in clinical trials. The switch from conventional IS to novel precision medicine approaches based on these drugs could prospectively and significantly improve MG care. In this review, we provide an overview of key immunopathogenetic processes underlying MG, and discuss on emerging biological drugs targeting them. We also discuss on future direction of research to address the need for patients' stratification in endotypes according with genetic and molecular biomarkers for successful clinical decision making within precision medicine workflow.